Avaliação da acessibilidade espacial no Parque João Goulart, Santa Rosa, RS - Klein, Pâmela (2019)
People with disabilities and reduced mobility, beyond the medical and individual perspective, associate themselves to a structural and social perspective, where the interaction environment has a huge impact on the experience and the extension of their mobility difficulties. Studies yet indicate the growth of this group, due to the advance of life expectancy, an increase of the indexes of chronic diseases and also to transit and work-related accidents. This group of people face several difficulties, since it is noticed the vast number of physical and spatial barriers in the built environment. Among the restrictions faced by this group is public leisure, one of the most acclaimed rights in society. It is frequent, in Brazilian cities, to find open public leisure places that present inadequate infrastructure to its users, due to the lack of accessibility, that causes exclusion situations, embarrassment and violate their right of having access to leisure. This work aims to evaluate the spatial accessibility at João Goulart Park, in Santa Rosa, state of Rio Grande do Sul, proposing applicable guidelines to parks in general, focusing on the spatial accessibility of the visually impaired, physically disabled and elderly, target audience for being city’s expressive groups, in number of people. The analysis considers spatial accessibility components defined as orientation, usage, displacement and communication. The adopted methodology, by means of direct observation, was based on the application of technical spreadsheets supported on regulations that provide information about the place. Besides that, interviews were conducted with the target audience, applied to Park users as well as in other parts of the city. The main results show that the spaces at João Goulart Park are not accessible for the community in its entirety, presenting issues related to all components of the spatial accessibility, where the results of technical spreadsheets are more restrictive, compared to the perception of the users. In relation to the public, the elderly present themselves as the best attended group, followed by the physically disabled and finally the visually impaired. The reasonable accessibility conditions result from weaknesses that can be reversed through measures that take into consideration the results from this research work.